Studi Pembuatan Biskuit Tepung Tulang Ikan Tenggiri Dengan Formulasi Berbeda Sebagai SUmber Kalsium Dan Fosfor - Ahyani Ridhayani; Rohimah Siregar; Lucia Dewi Indrayani Manurung; Nurhayati Nurhayati (Universitas Pahlawan Tuanku Tambusai, 2023)
Many people do not know the benefits and processing of fish bones, so the fish bones are thrown away and only become waste. One of the efforts to utilize this waste is to process fish bone waste into bone meal in making biscuits made from mackerel fish bones. This study aims to determine the acceptable formulation of wheat flour and mackerel bone meal by panelists in the manufacture of mackerel bone meal biscuits through the panelist's preference test (hedonic) and to determine the highest value of calcium and phosphorus of mackerel fish bone flour biscuits. This study used a randomized block design (RBD) method with one factor, namely the concentration of mackerel bone meal which consisted of 4 treatment levels, the ratio between wheat flour and mackerel bone meal was 100:0 g (A1), 95:5 g (A2). , 90:10 g (A3), 85:15 g (A4). The best formulation results based on the hedonic (liking) test were treatment A3 (7.67) with a very high level of liking. Meanwhile, the highest levels of calcium and phosphorus were in the A4 treatment with respective values of 3.3406 and 1.3573. This shows that the formulation of 90 g of wheat flour and 10 g of mackerel fish bone flour made the biscuits very liked by the panelists. Meanwhile, the more mackerel bone meal added, the greater the calcium and phosphorus value of the biscuits. Keywords: mackerel fish bone meal, biscuits, hedonic, calcium, phosphorus